Hold paramount the engineer's responsibility to society - Vesilind, P. Aarne; Gunn, Alastair S (Cencage Learning, 2011)
This book served as an excellent introduction to a wide variety of ethical issues. It also provided an excellent introduction to the practice of civil engineering covering the concepts of professional registration, bidding, design review etc. and gave the students an opportunity to practice their communication skills